Sensory and Nutritional Composition of Retort-pouched Rabbit Meat Rendang - Chua, Celine; binti Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2023)
Rabbits are classified into eight genera in the Leporidae family and are found all over the globe. In recent years, convenient food such as ready-to-eat food product which was packed into a retort pouch was popular in the market.Thus, by developing the rabbit meat which is packed in a retort pouch, the consumer’s time in meal preparation can be reduced and is convenient to eat without additional preparation. The objectives of this study were to formulate, evaluate consumer acceptance, and determine physicochemical properties and nutritional composition of the accepted product. The consumer acceptance was evaluated based on descriptive and affective tests with four product formulations tested. The physicochemical properties on moisture content, colour and pH were highlighted, meanwhile nutritional composition on protein, fat, ash, mineral, carbohydrates and energy content were determined. The formulation of sample coded with 450was highly accepted in descriptive and affective tests with 4.7 and 8.15 mean scores, respectively. The nutritional composition of rendang rabbit meat was 25.7g/100g in protein content, 13.7g/100g in fat content, 5.5g/100g in ash content, 1.09mg/100g in iron content, 465mg/100g in potassium content, 743mg/100g in sodium content and 370mg/100g in phosphorus content indicated that it has high protein content and ash content and has low fat content. While the moisture content was 50.5g/100g, indicated it has low moisture content after the long hours of rendang cooking process. The result of L* values =, a* values = 7.100.48 and b* values = and pH values of 5.68 showed that it has acceptable eating quality by panellists.